Beyond Stop Disasters 2.0: an agenda for exploring the contribution of video games to learning about disasters. (3rd April 2017) - Gampell, Anthony Viennaminovich; Gaillard, JC; Parsons, Meg; Fisher, Karen
ABSTRACT: With the increasing popularity of video games over the last few decades, a significant research area for disaster studies has presented itself. Preliminary disaster video game research deconstructed a multitude of disaster video games from various international organisations (e.g. UNESCO, UNISDR), governments (e.g. Canada), non-government organisations (e.g. Save the Children, Christian Aid), researchers and mainstream disaster video games. This research demonstrated that video games have an ability to convey messages regarding disaster and disaster risk reduction (DRR), including portrayals of hazards, vulnerabilities, capacities and numerous disaster discourses. Yet, there is a paucity of studies on these games in the disaster research literature. This review situates the foundations of disaster video game research within the realm of disaster studies, exploring concepts of disaster risk including hazards, vulnerability, capacities and methods of DRR. The review also works to link video games to disaster studies through the sphere of disaster risk education, participation and the learning theory of constructivism. This review sets the framework to enable adequate exploration of disaster video games in a way that could potentially contribute to DRR learning strategies of the future, with video games becoming a new cadre to the existing DRR tool kit.